Edaphoclimatic factors in the production and quality of Saboya grass (Holcus lanatus L.) in the highland of Nariño - Apráez, Edmundo; Gálvez, Arturo; Apraez, Julian (Revista de Ciencias Agrícolas, 2019)
Dairy farming in the department of Nariño depends mainly on the availability of forage. In this regard, the nutritional quality and production of this resource are affected by climatic conditions. This research aimed to establish the incidence of edaphoclimatic factors on the production and quality of Saboya grass (Holcus lanatus L.) in the highland of Nariño. The study was conducted in three zones: zone 1) three towns of the municipality of Guachucal located at 3050-3300 m.a.s.l; zone 2) three towns of the municipality of Ipiales at 2800–3049 m.a.s.l.; zone 3) three towns of the municipality of Pasto at 2500-2650 m.a.s.l. We sampled Saboya grass plots without tillage where we measured climatic, agronomic, edaphic, and bromatological variables in order to determine the degree of correlation among them. The quantitative variables were analyzed through principal component analysis (PCA) and the qualitative variables through a multiple correspondence analysis (MCA). We concluded that the highest yield of Saboya grass (H. lanatus) at an altitude between 2800 and 3049 meters requires loose soil, an organic matter content of 5-6%, and a pH of 6 to 7. In addition, this grass grows (H. lanatus) well at a temperature of 10°C, 83% relative humidity, 800 to 900 mm of annual rainfall, and 25 klx of luminosity. On the other hand, at an altitude range of 3050-3300 meters above sea level, Saboya grass requires loose soil, an organic matter content over 10%, and pH of 5 to 6. It is well-adapted to a temperature of 10 to 12°C, 86.28% relative humidity, and rainfall of 923 mm per year.